FEASIBILITY INVESTING IN DEVELOPMENT PROJECTS CITRA HARMONI SHOP (PT CIPUTRA TBK)FEASIBILITY INVESTING IN DEVELOPMENT PROJECTS CITRA HARMONI SHOP (PT CIPUTRA TBK) - Anna Rumintang Nauli (Journal of Civil Engineering Science and Technology (CI-TECH), 2022)
Investment is a commitment to several funds or other resources carried out at this time, intending to obtain some benefits in the future. Investments can be associated with a wide variety of activities. Investing many funds in real assets (land, gold, machinery, or buildings) or financial assets (deposits, stocks, or bonds) is an investment activity that is generally carried out, especially for developers. So that before stepping into the development stage, it is necessary to conduct a feasibility study first to be able to state whether or not the development of a project is continued. This study takes a case study of RUKO (Rumah Toko) in the Sidoarjo area, namely Ruko Citra Harmoni, and in its financial analysis uses discounted cash flow analysis. From the analysis results obtained: (1) Total development costs (development costs) calculated from the cost of DC phase, I added to the DC phase II is Rp. 3,831,665,014, -. (2) Loan from 60% development cost (DC) which is Rp. 2,298,999,008,-, while the remaining 40% of Rp.1,532,666,006,- is equity. So that the Debt Service from the loan that must be paid annually is Rp. 285,075,877,-. (3) The net present value obtained is Rp. 1,389,027,781,- during 30 years. (4) Internal rate of return (IRR) = 18.47 % > discount factor (DF) 16%. (5) Payback period is 23.8 years. (6) BCR > 1, i.e. 1.29 > 1. So from the several assessments above it can be stated that the Royal Business Regency Ruko Palm Project is feasible to work on and carry out construction